2014
DOI: 10.4028/www.scientific.net/jnanor.27.15
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Structural and Mechanical Properties of Nanocrystalline TiAlSiN Gradient Coatings

Abstract: A study of the structural and mechanical properties of nanocrystalline TiAlSiN gradient coatings deposited by cathodic arc deposition techniques at 500 °C and post-annealed at 525 °C is presented. Analysis of the coatings, chemical composition and microstructure revealed that the coatings have a structure based on (Ti, Al)N nanocrystals with an average size of 10 nm embedded in an amorphous Si3N4 phase. The study of the mechanical properties showed that post-annealing causes improvement and increase of the coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The microstructure of the examined coatings has been thoroughly investigated in previous studies [3,4], revealing the dispersion of AlN and TiN nanocrystals with a grain size of 10 nm, in a Si 3 N 4 amorphous phase. This particular microstructure results in a maximum nanohardness value of 48 GPa and a Young modulus of 560 GPa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The microstructure of the examined coatings has been thoroughly investigated in previous studies [3,4], revealing the dispersion of AlN and TiN nanocrystals with a grain size of 10 nm, in a Si 3 N 4 amorphous phase. This particular microstructure results in a maximum nanohardness value of 48 GPa and a Young modulus of 560 GPa.…”
Section: Methodsmentioning
confidence: 99%
“…Especially, their high hardness values and their excellent tribological performance renders them attractive as anti-wear coatings for engineering applications [1,2]. Depending on their microstructure growth, they can be classified as nanocomposite, nanoscale multilayer, superlattice and nanocrystalline gradient coatings [3][4][5][6][7][8]. Especially in the case of the TiAlN systems, recent studies argued on their enhanced mechanical properties [9,10] and their superior performance under in-service severe surface loading [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The high-energy resolved XPS spectra of core-levels (Figs. [5][6] show that Fe in an as-prepared sample (from AISI430 substrate) is strongly oxidized and has the Fe 3+ oxidation state. After Ar TiN [24], Si 3 N 4 [25] and AlN [26].…”
Section: Xps Spectramentioning
confidence: 99%
“…It has also been found that a-Si 3 N 4 -boundary phase in TiAlSiN coatings prevents diffusion of oxygen along the grain boundaries [4]. To date, a great body of research in TiAlSiN coatings has been focused mostly on the development of various deposition methods and on studying their microstructure, mechanical properties, and oxidation resistance [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a low temperature PECVD process would not appear to be a feasible approach for the synthesis of TiSiCN nanocomposite, unless followed by annealing at temperature high enough for the spinodal hardening process to occur. There are only a few instances where a similar processing strategy has been attempted with nanocomposites, such as (Al1-xTix) N/a-Si3N4 [14] and TiAlSiN [15], also in view of enhancing the coating-substrate adhesion. Accordingly, the primary objective of the present work was to investigate the effects of annealing on TiSiCN self-lubricant nanocomposite coatings deposited on AISI H13 steel substrate via pulsed-DC PECVD.…”
Section: Introductionmentioning
confidence: 99%